Recent Approaches of Ocular Disease and Its Herbal Product Treatment: An Updates - Butola, Kanchan; Bisht, Vijaylaxmi; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2023)
One of the most common causes of permanent vision loss is glaucoma. Damage to the optic nerve and retinal ganglion cells, the root cause of visual field impairment, is typically the result of elevated intraocular pressure. Some patients' illness worsens even when treated with eye medications that reduce intraocular pressure. The pathophysiology of glaucoma is not only thought to involve mechanical and vascular dysfunctions of the eye, but also oxidative stress, neuroinflammation, and excitotoxicity. Therefore, natural compounds with antioxidant and anti-inflammatory qualities may offer a different strategy for treating glaucoma. This review summarizes the most up-to-date preclinical and clinical research on natural compounds that have been proven to contain neuroprotective characteristics for retinal ganglion cells and, consequently, may be useful in the treatment of glaucoma. Baicalein, forskolin, marijuana, ginsenoside, resveratrol, and hesperidin are all effective at lowering intraocular pressure. On the other hand, antioxidant, anti-inflammatory, and anti-apoptosis mechanisms are among those through which Ginkgo biloba, More research is needed to determine whether natural items can be used as a safe and effective treatment for glaucoma.